The Possible Anti-nociceptive Effect of Troxerutin and Neural Interactions Using Formalin and Writhing Tests in Mice - Farima Jafari-Tirabadi; Shahin Hassanpour; Ahmad Asghari (Avicenna Journal of Medical Biochemistry, 2023)
Background: Previous reports suggest flavonoids as potent analgesic compounds. Objectives: Based on these observations, the present study investigated the anti-nociceptive action of troxerutin and neural interactions with opioidergic, serotoninergic, and nitrergic systems in mice. Methods: A total of 340 male mice were randomly divided into 2 categories. Each category included four experiments with four groups. In the first experiment of formalin examination, the animals intraperitoneally received saline and troxerutin (50, 150, and 300 mg/kg). In the second experiment, the animals received saline, naloxone (2 mg/kg), troxerutin (300 mg/kg), and troxerutin+naloxone. In the third and fourth experiments, L-NAME (L-NG-Nitroarginine methyl ester) and cyproheptadine were injected. In this test, formalin was injected and paw licking time (pain sense) was recorded. In the writhing test, experimental groups were treated similarly and the mice were injected with acetic acid. Then, the inhibition of the writhing movements was recorded. Results: According to the findings, troxerutin decreased pain in the formalin test and writhing movements in the writhing test (P=0.001). Naloxone and troxerutin decreased licking time and writhing movements (P=0.001). L-NAME+troxerutin significantly diminished the anti-nociceptive effect of troxerutin on paw licking and inhibited pain response (P=0.001). Conclusion: These results suggested that troxerutin decreases inflammatory pain in mice, and this effect is mediated by opioidergic and nitrergic systems.